2010
DOI: 10.1007/s12350-010-9247-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an accurate assessment of myocardial salvage by comparing functional and perfusion abnormalities in post-reperfusion gated SPECT

Abstract: Background. Because of persistent stunning, post-treatment functional abnormalities could identify the initial risk area. The study aims to detect myocardial salvage using postrevascularization gated SPECT in acute myocardial infarction (AMI) treated by reperfusion therapy.Methods. In 36 AMI patients, we performed a first gated SPECT injecting 99mTc-sestamibi before primary percutaneous coronary intervention (PCI), and a second 5 days later. The salvage index defined by the two perfusion images was compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This model resulted in a high concordance between myocardium atrisk area at the first gated SPECT examination and estimated myocardium at-risk area at the second examination. Automatic quantification of the extent of perfusion and wall motion abnormalities, which we performed in our study, is a more reproducible method than analysis of the discrepancy between perfusion and thickening assessed subjectively in an earlier phase of AMI (12), and this can partially explain why…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This model resulted in a high concordance between myocardium atrisk area at the first gated SPECT examination and estimated myocardium at-risk area at the second examination. Automatic quantification of the extent of perfusion and wall motion abnormalities, which we performed in our study, is a more reproducible method than analysis of the discrepancy between perfusion and thickening assessed subjectively in an earlier phase of AMI (12), and this can partially explain why…”
Section: Discussionmentioning
confidence: 80%
“…To estimate the area of myocardium at risk using only variables from the second gated SPECT examination, we set up several models. (12). The best model, permitting the most correct estimate of the area of myocardium at risk, included AMI location, extent of the perfusion defect, and extent of the wall motion abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study imaging was performed at an average of 5 days with a range of 2-8 days. Previous work from our laboratory cited by Sciagra et al 17 indicated that measurement of infarct size at 48 hours would over-estimate infarct size in some patients. 18 Unfortunately, myocardial stunning has already started to resolve at that time in some patients.…”
mentioning
confidence: 88%